A review on reducing the incidence of postoperative ileus by chewing gum, consuming coffee or warm water post abdominal surgery - Firmanti, Tria Anisa; Sukartini, Tintin; Krisnana, Ilya (MEDISAINS, 2020)
Background: Postoperative ileus is the main complication post abdominal surgery; it signs two or more periods of vomiting and nausea, intolerance of diet more than 24 hours, inability to pass flatus more than 24 hours, and abdomen distension. Several studies are stating that interventions chewing gum, consuming coffee, and drinking warm water can reduce the incidence of postoperative ileus.Objective: Collects the evidence for effect chewing gum, consuming coffee, and warm water to reduce postoperative ileus.Method: This systematic review is arranged based on literature studies from five databases last five years, such as Scopus, Sciencedirect, Proquest, and Oxford, with the comprehensive survey, which conducted according to the guidelines in the PRISMA. We searched for studies with the keyword "chewing gum" OR "coffee" OR "warm water" AND "postoperative."Result: We selected 215 articles from an electronic database, and 17 articles with Randomized Control Trials (RCTs) method included. The sampling of selected items in this systematic review carried for five months to 1 year, from January to December 2010 - 2017, obtained 20 to 975 samples. There was a significant effect of chewing gum, consuming coffee, and warm water reduced postoperative ileus incidence without side effects.Conclusion: Chewing gum, consuming coffee, and warm water, are effective, safe, and not expensive to reduce the incidence of postoperative ileus and improve recovery post abdominal surgery.